The political economy of Gulf defense establishments - Barany, Zoltan D. (Cambridge : Cambridge University Press, 2021)
The six monarchies on the Arabian Peninsula have devoted enormous sums to defense in past decades. Nevertheless, the gap between their expensive armaments and their capacity to deter aggression and/or project military strength has narrowed but little in that time. This Element takes a political economy approach and argues that structural factors inherent in the Gulf states' political systems prohibit civilian oversight of the defense sector and are responsible for this outcome. Lax restraints on military outlays, in turn, enable widespread corruption, lead to large-scale waste, and account for the purchasing of unneeded, unsuitable, and incompatible weapons systems. The Element explores the challenges caused by plummeting oil prices and the resulting budget cuts and considers the development of domestic defense industries in Saudi Arabia and the UAE, intended as a part of their economic diversification program. The setbacks of the Saudi-led coalition's on-going war in Yemen starkly illustrate the narrative.
Title from publisher's bibliographic system (viewed on 05 Feb 2021).
Keywords: Defense industries -- Persian Gulf Region